2015
DOI: 10.1080/21505594.2015.1060396
|View full text |Cite
|
Sign up to set email alerts
|

Tackling tuberculosis: Insights from an international TB Summit in London

Abstract: Tuberculosis (TB) poses a grave predicament to the world as it is not merely a scientific challenge but a socio-economic burden as well. A prime cause of mortality in human due to an infectious disease; the malady and its cause, Mycobacterium tuberculosis have remained an enigma with many questions that remain unanswered. The ability of the pathogen to survive and switch between varied physiological states necessitates a protracted therapeutic regimen that exerts an excessive strain on low-resource countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Hence, enlargement of novel and effective therapies to battle mycobacteria are urgently required (3, 4). Mtb is an intracellular pathogen able to survive indefinitely under unfavorable conditions inside primary host immune cells, preferably residing in human alveolar macrophages (5, 6). Several studies have recently shown that features such as its high infectivity, slow growth, and complex cell-wall structure, make M. tuberculosis a major challenge to be faced, since the specific mechanisms that reinforce the high virulence of Mtb remain largely unknown (4, 7).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, enlargement of novel and effective therapies to battle mycobacteria are urgently required (3, 4). Mtb is an intracellular pathogen able to survive indefinitely under unfavorable conditions inside primary host immune cells, preferably residing in human alveolar macrophages (5, 6). Several studies have recently shown that features such as its high infectivity, slow growth, and complex cell-wall structure, make M. tuberculosis a major challenge to be faced, since the specific mechanisms that reinforce the high virulence of Mtb remain largely unknown (4, 7).…”
Section: Introductionmentioning
confidence: 99%
“…1 This has provided the much-needed impetus for the discovery and development of novel, more effective and safer anti-tubercular chemotherapeutics. [2][3][4] However, there is a high attrition rate of lead molecules passing from preclinical development to Phase I clinical studies. 5 This has led to a shortage of novel molecules available for further development and incorporation into successful anti-tubercular therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The 3 day event was well attended with representatives from universities and government agencies from all over the world. The informative oral presentation and poster sessions were categorised for a systematic discussion on the different aspects of TB as is discussed in more detail in the following sections of the report.…”
Section: Introductionmentioning
confidence: 99%